Peran Ibu sebagai Edukator dan Konsumsi Sayur Buah pada Anak - Putri Atika Afif; Sri Sumarmi (Amerta Nutrition, 2017)
Background : The consumption of vegetable and fruit among school age children is inadequate and below WHO recommendation (400gr/day).There are many important factors influence the children’s consumption of vegetable and fruit such as mother’s role and fruit and vegetable stock in household. Objectives: To analyze the relationship between mother’s role and fruit and vegetable stock in household with the children’s consumption level of fruit and vegetable. Method : Research with cross sectional method was conducted in SDN Kandang Tepus 01 and SDN Kandang Tepus 02 Senduro  village, Lumajang regency with sample 41 children grade 4 and 5 with their mother. Variable that observed in this research are mother’s role as educator and inisiator  of vegetable and fruit stock in home and the children consumption of vegetable and fruit. Data was collected with interview using questionnaire instrument and semi quantitative  food frequency . Result : Children who consume vegetable and fruit based on WHO recommendation 400 gr/day was 17.1%. Chi-square test showed that there was relathionship between mother’s role as educator (p-value = 0.014) and stock of vegetable and fruit in household (p-value = 0.003) with the children’s consumption of vegetable and fruit (p-value = 0.028). But there was no relationship between mother’s role as initiator with children’s consumption of vegetable and fruit. Conclusion: Mother’s role as educator related to children’s consumption of vegetable and fruit because its depend on stock of fruit and vegetable in household.ABSTRAK Latar Belakang: Konsumsi sayur dan buah pada anak usia sekolah masih tergolong rendah dan belum memenuhi anjuran WHO sebesar 400 gr/hari. Banyak faktor yang mempengaruhi konsumsi sayur buah pada anak, terutama terkait peran ibu dan ketersediaan sayur buah di rumah.Tujuan: Menganalisis hubungan peran ibu dan ketersediaan sayur buah di rumah dengan tingkat konsumsi sayur buah pada anak usia sekolah.Metode: Penelitian dengan desain cross sectional dilakukan di SDN Kandang Tepus 01 dan SDN Kandang Tepus 02 Desa Senduro Kabupaten Lumajang dengan jumlah sampel 41 anak kelas 4 dan 5 beserta ibu. Variabel yang diamati dalam penelitian ini adalah peran ibu sebagai edukator dan inisiator untuk buah dan sayur, ketersediaan sayur dan buah di rumah dan konsumsi sayur dan buah pada anak. Pengumpulan data dilakukan dengan metode wawancara dengan instrumen kuesioner dan food frequency semi kuantitatif.Hasil: Besar presentase anak yang mengonsumsi sayur buah sesuai anjuran 400 gr/hari yaitu 17,1% dari 41 anak. Hasil uji chi-square menunjukkan ada hubungan antara peran ibu sebagai edukator (p-value = 0,014) dan ketersediaan sayur buah di rumah (p-value = 0,003) dengan konsumsi sayur buah pada anak. Ada hubungan peran ibu sebagai edukator dengan ketersediaan sayur buah di rumah (p-value = 0,028). Namun tidak ada hubungan antar peran ibu sebagai inisiator dengan konsumsi sayur buah pada anak.Kesimpulan: Peran ibu sebagai edukator berhubungan dengan konsumsi sayur buah pada anak karena terkait dengan penyediaan sayur dan buah di rumah.